Genome-wide identification of Schistosoma japonicum microRNAs using a deep-sequencing approach. - Jian Huang (Public Library of Science (PLoS), 2009)
Background Human schistosomiasis is one of the most prevalent and serious parasitic diseases worldwide. Schistosoma japonicum is one of important pathogens of this disease. MicroRNAs (miRNAs) are a large group of non-coding RNAs that play important roles in regulating gene expression and protein translation in animals. Genome-wide identification of miRNAs in a given organism is a critical step to facilitating our understanding of genome organization, genome biology, evolution, and posttranscriptional regulation. Methodology/principal findings We sequenced two small RNA libraries prepared from different stages of the life cycle of S. japonicum, immature schistosomula and mature pairing adults, through a deep DNA sequencing approach, which yielded approximately 12 million high-quality short sequence reads containing a total of approximately 2 million non-redundant tags. Based on a bioinformatics pipeline, we identified 176 new S. japonicum miRNAs, of which some exhibited a differential pattern of expression between the two stages. Although 21 S. japonicum miRNAs are orthologs of known miRNAs within the metazoans, some nucleotides at many positions of Schistosoma miRNAs, such as miR-8, let-7, miR-10, miR-31, miR-92, miR-124, and miR-125, are indeed significantly distinct from other bilaterian orthologs. In addition, both miR-71 and some miR-2 family members in tandem are found to be clustered in a reversal direction model on two genomic loci, and two pairs of novel S. japonicum miRNAs were derived from sense and antisense DNA strands at the same genomic loci. Conclusions/significance The collection of S. japonicum miRNAs could be used as a new platform to study the genomic structure, gene regulation and networks, evolutionary processes, development, and host-parasite interactions. Some S. japonicum miRNAs and their clusters could represent the ancestral forms of the conserved orthologues and a model for the genesis of novel miRNAs.